2007
DOI: 10.1007/s10620-006-9107-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Cholelithiasis: Is Cholecystectomy Really Needed? A Critical Reappraisal 15 Years After the Introduction of Laparoscopic Cholecystectomy

Abstract: Asymptomatic cholelithiasis is increasingly diagnosed today, mainly as a result of the widespread use of abdominal ultrasonography for the evaluation of patients for unrelated or vague abdominal complaints. About 10-20% of people in most western countries have gallstones, and among them 50-70% are asymptomatic at the time of diagnosis. Asymptomatic gallstone disease has a benign natural course; the progression of asymptomatic to symptomatic disease is relatively low, ranging from 10-25%. The majority of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
2
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(160 citation statements)
references
References 108 publications
(156 reference statements)
4
129
2
11
Order By: Relevance
“…At the age of 65, about 30% of women have GS, and by the age of 80 years, 60% of both males and females have GS. The large majority of these (70-85%) are asymptomatic [4]. In India, Khuroo et al [5] reported a 6.1% (men 3.1% and women 9.6%) prevalence of GS in subjects above 15 years of age from Kashmir in northern India; 94% of these were asymptomatic at the time of diagnosis.…”
Section: Burden Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…At the age of 65, about 30% of women have GS, and by the age of 80 years, 60% of both males and females have GS. The large majority of these (70-85%) are asymptomatic [4]. In India, Khuroo et al [5] reported a 6.1% (men 3.1% and women 9.6%) prevalence of GS in subjects above 15 years of age from Kashmir in northern India; 94% of these were asymptomatic at the time of diagnosis.…”
Section: Burden Of the Problemmentioning
confidence: 99%
“…Factors that have been reported to confer a higher risk of progression from asymptomatic to symptomatic disease and/or complications include age <55 years, smoking, female sex, greater body weight, presence of three or more GS, and presence of floating stones [7,18]. Other workers have observed that life expectancy >20 years, calculi >2 cm in diameter, calculi <3 mm and patent cystic duct, nonfunctioning GB and perioperative detection of incidental stones are the risk factors for progression to symptomatic/ complicated GS disease [4,19] Higher risk of developing GBC has been reported in patients with GS and associated polyps >1 cm, calcified GB (13-22%), large stones >3 cm (10 times risk) [20,21], GB packed with stones [22] and ethnic groups in highincidence GBC areas [21,23,24].…”
Section: Risk Stratificationmentioning
confidence: 99%
“…It is the most common abdominal surgical disease in the elderly, with prevalence of 21.4% for the aged 60 to 69 years and 27.5% in individuals aged over 70 years 2 . The symptoms are absent between 50% and 77% of cases 3,4 , but presentments of worsening and complicated biliary calculi are frequent.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…perforated gall bladder), choledocholithiasis, other gall bladder pathologies like polyps, those having concurrent hepato-biliary pathology with suspicious/risk for malignancy, porcelain gallbladder, patients with large >3 cm stones, transplant patients and patients with chronic hemolytic conditions were excluded from the study. 5 Pain was evaluated for localization, radiation, severity, intensity alleviating and aggravating factors. The USG findings, endoscopic findings, and histopathology of the patients with gastric/duodenal biopsies findings were evaluated to decide a treatment plan for the patients.…”
Section: Methodsmentioning
confidence: 99%